2022
DOI: 10.3390/w14030334
|View full text |Cite
|
Sign up to set email alerts
|

Base Flow Variation and Attribution Analysis Based on the Budyko Theory in the Weihe River Basin

Abstract: The composition and change of runoff are closely related to climate change and human activities. To design effective watershed water resources management measures, there is a need for a clear understanding of the impact of climate change and human activities on baseflow and surface runoff. The purpose of this essay is to quantify their impact on the annual total stream flow, surface runoff, and base flow in the Weihe River Basin (WRB) using a two-stage annual precipitation partitioning method, wherein the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…However, urbanization and industrialization have increased the pressure on the eco-environment quality in the Weihe River Basin. In addition, soil erosion, serious water pollution, and ecological degradation limit the sustainable development of the study area [ 56 , 57 , 58 , 59 ]. The combined influence of multiple factors has accelerated the urgent need to improve the eco-environment quality in the Weihe River Basin.…”
Section: Introductionmentioning
confidence: 99%
“…However, urbanization and industrialization have increased the pressure on the eco-environment quality in the Weihe River Basin. In addition, soil erosion, serious water pollution, and ecological degradation limit the sustainable development of the study area [ 56 , 57 , 58 , 59 ]. The combined influence of multiple factors has accelerated the urgent need to improve the eco-environment quality in the Weihe River Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have discussed the impacts of climate change and human activities on hydrological change, mainly in arid and semi-arid regions [18,58,65,69,70]. Because these regions are located inland and have less precipitation, the impact of climate change on the hydrological environment is small, and thus the ecological environment and human daily water use depend strongly on rivers.…”
Section: Attribution Analysis Of Baseflow Changementioning
confidence: 99%
“…Baseflow change mainly depends on the rainfall process, soil and geological indicators, and hydrological characteristics of the basin, and is also affected by the spatial distribution of vegetation and evapotranspiration in the basin; baseflow also increases or decreases depending on human activities [9][10][11]. Mu et al [12] used a single-parameter digital filtering method to separate baseflow in the Weihe River basin, and found that climate change dominated the surface streamflow variations, while human activities controlled the baseflow variations. Wilby et al [13] calculated the influence of climate change on baseflow using a large-scale hydrological model and found that the dominant factors of the change in baseflow were different in different periods.…”
Section: Introductionmentioning
confidence: 99%